1989
DOI: 10.1128/aem.55.7.1801-1807.1989
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Biomass by Ultrasonic Measurements

Abstract: The quantitative determination of biomass in a suspension by means of ultrasound velocity is a simple and on-line-applicable method. Such an ultrasonic sensor offers the advantage of being long-term stable, reliable, and sterilizable. In this paper we present sound velocity measurements made with different microorganisms. The experimental results which we have obtained with an impulse-echo method will be compared with theoretical predictions and discussed with respect to previous findings (Y. Ishimori, I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…The biomass concentrations can also be determined from the difference between the velocity of ultrasonic sound in the suspension and in the microorganism-free solution (Blake-Coleman et al, 1986;Zips and Faust, 1989). However, the need for a microorganism-free reference requires either the withdrawal of the sample or in situ measurement of the background signal (Olsson and Nielsen, 1997).…”
Section: Conductivitymentioning
confidence: 99%
“…The biomass concentrations can also be determined from the difference between the velocity of ultrasonic sound in the suspension and in the microorganism-free solution (Blake-Coleman et al, 1986;Zips and Faust, 1989). However, the need for a microorganism-free reference requires either the withdrawal of the sample or in situ measurement of the background signal (Olsson and Nielsen, 1997).…”
Section: Conductivitymentioning
confidence: 99%
“…Ultrasonic velocity rose with increasing cell concentrations in the range of 0-15 g/L. Furthermore, the ultrasonic attenuation increased with increasing concentrations of Saccharomyces tandae [10]. Likewise, Endo et al measured the sound intensity level using a piezoelectric sensor immersed in a microbial suspension and observed decreasing output voltage with increasing cell concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic attenuation and velocity are influenced by the concentration of particles [6][7][8] and biological cells [9][10][11] in suspensions. Dukhin et al found an increase of ultrasonic velocity and attenuation with rising volume fraction of red blood cells [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geralmente, o método ultra-sônico mais empregado é baseado na medida da velocidade de propagação longitudinal, através da estimativa do tempo de vôo da onda no mosto de fermentação, que visa o cálculo da densidade e concentração alcoólica durante o processo de conversão dos carboidratos em etanol (RESA et al, 2004). No entanto, a monitoração ultra-sônica mediante estimativas da velocidade de propagação em relação às taxas de crescimento dos microorganismos (leveduras), considerados como o agente mais importante na obtenção do álcool (PACHECO, 2010), raramente se vê reportada na literatura (ZIPS; FAUST, 1989), o que reflete as limitações do parâmetro velocidade, e a incapacidade do parâmetro na avaliação da heterogeneidade do meio, devido à pequena variação da velocidade durante a fermentação, que dificilmente descreve a cinética de propagação dos agentes de transformação. Esta por sua vez está diretamente relacionada com a qualidade e rendimento do produto no processo fermentativo.…”
Section: Justificativaunclassified